Community Involvement on Caldera Toba Geopark Development Case Study: Pusuk Buhit Area, Samosir Regency - Hotasina Silaen, Cathelya Yosephine (E-Journal of Tourism, 2017)
Geopark is a geological area, including the specific features of the geologically significant, rare or in the form of beauty which also has ecological value, archaeological, historical and cultural to local economic development through conservation, education and tourism. The most important thing of geopark development is local involvement by making a collaboration between government and locals, such as in Caldera Toba National Geopark. The existing collaboration between government and locals in this geopark, is formed simply as reciprocity, where they understand their position in the development of geopark and is willing to establish new relationships that equally benefit to them, even though there are some actors who deny the existence Caldera Toba Geopark. That kind of collaboration came up by mapping each actor role and position in every stage of geopark development, also ultimately how each of these actors collaborate in developing and operating Caldera Toba Geopark as a national and international tourism destination. The most interesting thing to be explored is how to collaborate geopark managerial issues with local culture. To involve the locals with their own entrenched culture, the government needs to create creative strategies and innovations to collaborate the locals, the government itself and the third party as well. This study lies in Pusuk Buhit Area, which has four geosites and located in Geoarea Samosir. Pusuk Buhit has its history of the starting of the old Bataknese people. Based on that history, Pusuk Buhit is inhabited by the old Bataknese family that have their pure Bataknese culture and its local wisdom. Beside their culture wisdom, this area is still affected by religious wisdom, such as Christianity and local religion, named Parmalim. To involve all stakeholders with their own interests, the government should construct the new institutional scheme for the future Caldera Toba Geopark,that has to be a collaboration instituional. By using stakeholder analysis for the mapping, with primary data collection methods in-depth interviews with some of the key actors, the author may interpret and assess the extent of the collaboration undertaken by each actor in developing Caldera Toba Geopark, as well as predict the suitable collaboration for managing Toba Caldera Geopark, as a strategy to make this geopark works.